The Completeness of Medical Record Documents to Improve The Service Quality at Puskesmas in Sukoharjo Regency - Astri Sri Wariyanti; Harjanti; Sri Sugiarsi (Proceeding of International Conference on Science, Health, And Technology, 2019)
Based on preliminary studies in four Puskesmas in the Sukoharjo District Health Office, which include Puskesmas Polokarto, Grogol, Sukoharjo, Bendosari, there are differences in the average value of completeness of medical record documents before and after accreditation. Before accreditation, the average value of completeness of documents was 66%, whereas after accreditation there was an increase in the value of completeness by 80%. This research was aimed at knowing the influence of medical record document completeness at Puskesmas in Sukoharjo regency. The hypothesis of this research is that there is influence between medical record document completeness before and after accreditation. This research was analitical research. The research was conducted in Puskesmas of Polokarto, Sukoharjo, Bendosari, and Grogol. The population was all outpatient medical record document in 2016 and 2018. The sample used was purposive sampling. The dependent variable in this research was the completeness of identity, important report, authentication, correct documentation dan the independent variable was the accreditation. The research instrument used were checklist and observation guidance. The data were collected through observation and interview to the head of medical record. The data were analyzed quantitatively through Wilcoxon test. The result of the research here was a significant increase in the average completeness of medical record documents on Authentication items by 26.37%. Stastistical test of Wilcoxon Signed Rank Test since the result of normality test showed that the data were not normal (p <0.05). the result shows that there is influence between medical record document completeness before and after accreditation with the value 0.001. The conclusion of this research is thecompleteness of outpatient medical record document improves after accreditation, so it needs regular socialization related to the officer obedience in filling the medical record document that the completeness can reach 100%